Detection and measurements of free ubiquitin in fixed cells and characterization of OTUB1 contribution to ubiquitin homeostasis - Prada Gomez, Luisa Fernanda, author; Cohen, Robert, advisor; Di Pietro, Santiago, committee member; Markus, Steven, committee member; Tamkun, Michael, committee member (Colorado State University. Libraries, 2020)
Post-translational modifications with Ubiquitin (Ub) have been found to participate in a wide range of cell functions, including protein degradation, endocytosis, regulation of gene expression and cell cycle progression. Therefore, regulation of free Ub levels is essential to ensure that enough Ub is available for conjugation, while excess Ub does not compete in the large number of processes that depend on binding to ubiquitinated proteins or polyUb. Not surprisingly, changes in Ub pool dynamics can affect the cell functions, and perturbations of free Ub levels have been reported to cause neurological and developmental disorders. Although there are techniques to measure Ub pools in vitro, visualization and quantification of free Ub inside individual cells has not been possible. One way to regulate the intracellular concentration of free Ub, is by means of Deubiquitinating enzymes (DUBs), however specific details about the regulatory mechanism are, in large part, unknown. Most studies about DUBs have focused on enzymatic activity and regulation in vitro, with only few reports on the regulation of Ub homeostasis in vivo. The role of OTUB1 in Ub homeostasis has been hypothesized because its catalytic activity is affected by the ratio of [Ub~E2] to [E2] in response to free Ub concentration. Interaction between OTUB1 and a subset of E2s can stimulate OTUB1 isopeptidase activity, whereas interactions with Ub~E2s can inhibit the ubiquitin transfer from the thioester Ub~E2 adduct. This dissertation describes the successful development of a technique to detect and quantify changes in free Ub levels in fixed cells using a high affinity binding protein. The method was used to quantify changes in Ub levels after proteasome and E1 inhibition and to establish the free Ub distribution in hippocampal neurons. It was shown also that OTUB1 activity is not directly involved in the regulation of free Ub levels under stress conditions. However, a new mechanism for regulation of UBE2D expression levels dependent on OTUB1 was identified. This mechanism is independent of proteasomal degradation and could possibly involve translational regulation.